Criminal Liability For Illegal Abortion In Indonesian And Islamic Law: a Comparative Study - Fahmi, Zul; Hasibuan, Affan Muhammad; Nasution, Roni Risky; Asrofi, Asrofi; Suroto, Suroto (Fakultas Syariah Institut Agama Islam Negeri Palu, 2025)
This study examines criminal liability for illegal abortion under Indonesian positive law and Islamic law by analyzing their normative foundations, common ground, and points of difference. Using a normative legal research method with a comparative approach, this study utilized primary sources, including the Criminal Code, Health Law, Qur’an, Hadith, classical fiqh literature, and MUI fatwas to map the rules and rationale of each system. The findings show that both legal frameworks expressly prohibit abortion without a valid reason, but differ in terms of rationale and sanctions. Indonesian law emphasizes formal legal protection of the right to life, with prison sentences of up to 15 years and fines of up to 1 billion rupiah. Islamic law frames abortion as a moral-religious offense, calibrating punishment to the development of the fetus: before 120 days, the perpetrator pays ghurrah, and after 120 days, abortion is equated with murder and punishable by qisas or diyat. Integrating textual interpretation with the maqasid sharia framework, this research contributes a nuanced comparative model that highlights how secular and religious norms can inform one another. This research underscores the need for legal harmonization, policymakers can enrich Indonesia’s regulatory regime by incorporating maqasid sharia principles such as staged medical review and psychosocial counseling into existing legislation to strike a balance between legal certainty, public health, and ethical imperatives. These insights pave the way for targeted reforms and empirical studies that assess the real-world impact of a harmonized, combined approach in reducing illegal unsafe abortion and promoting reproductive justice